THE SALES PLANNING IN THE AUTOMOTIVE BUSINESS: STRUCTURE OF PLANNING - D. Prokudin (Вестник университета)
The definition of sales planning is given, methods of planning and the structure of sales at the automotive companies are described. Some exceptional cases which can be met at the time of application of the sales plan are described.